Non-Axisymmetric dynamic response of imperfectly bonded buried fluid-filled orthotropic cylindrical shells due to incident shear wave - Dwivedi J.P.; Singh V.P.; Upadhyay P.C. (My University, 2025)
A theoretical analysis is presented of the non-axisymmetric dynamic response of an imperfectly bonded fluid-filled buried orthotropic pipeline subjected to a combination of SV- and SH-waves travelling in the surrounding medium of infinite extent. Numerical results have been presented for the case of an incident SV-wave only. An infinite cylindrical shell model including the effects of shear deformation and rotary inertia has been considered for the pipeline. The linear acoustic equation has been used for the wave propagation in the fluid inside the pipe. The results for a fluid-filled shell have been compared with those for an empty shell. The relative effects of fluid presence and the bond imperfection on the dynamic response have also been studied. © 1993 Academic Press Limited.